Intra-Arterial Thrombolysis Vs. Mechanical Thrombectomy in Acute Minor Ischemic Stroke Due to Large Vessel Occlusion - Sun, Dapeng; Huo, Xiaochuan; Raynald; Wang, Anxin; Mo, Dapeng; Gao, Feng; Ma, Ning; Miao, Zhongrong (Frontiers in Neurology, 2022)
Abstract Background: The efficacy and safety of mechanical thrombectomy (MT) in acute large vessel occlusions (LVO) patients with minor stroke (NIHSS < 5) remains undetermined. We aimed to compare the efficacy and safety of intra-arterial thrombolysis (IAT) alone versus MT for LVO patients with minor stroke. Methods: Patients were selected from the ANGEL (prospective multicenter study of Acute ischemic Stroke Cooperation Group of Endovascular Treatment) registry and divided into MT group and IAT alone group. We compared the outcome measures between the two groups, including 90-day functional outcome evaluated by the modified Rankin Scale (mRS), final recanalization level, intracranial hemorrhage, and mortality within 90-days by logistic regression models with adjustment. Besides the conventional multivariable analysis, we also constructed a propensity score for adjustment as the sensitivity analysis to confirm our results (the propensity score was derived using a logistic regression model). Results: A total of 120 patients, 63 received IAT alone and 57 received MT as the first-line treatment strategy. As compared to MT group, patients in IAT alone group were associated with higher chance of 90-day mRS 0-2 (93.7% vs. 71.9%, odds ratio [OR] = 4.75, 95% confidence interval [CI]: 1.20 – 18.80, P = 0.027), high chance of 90-day mRS 0-3 (96.8% vs 86.7%, OR = 11.35, 95%CI: 1.93-66.86, P = 0.007), shorter median time from puncture to recanalization (PTR) (60 min vs. 100 min, β = -63.70, 95%CI: -81.79- -45.61, P < 0.001), lower chance of any ICH within 48 h (3.2% vs. 19.3%, OR = 0.15, 95%CI: 0.03 – 0.79, P = 0.025), and lower chance of mortablity within 90 days (1.6% vs. 9.2%, OR = 0.05, 95%CI: 0.01- 0.57, P = 0.016). Likewise, the sensitivity analysis showed the robustness of the primary analysis. Conclusions: Compared with MT, IAT may improve 90-day clinical outcomes, with decreased ICH rate and mortality in LVO patients with minor stroke.